A novel anti-melanogenic agent, KDZ-001, inhibits tyrosinase enzymatic activity. Issue 2 (February 2018) - Hwang, Kyu-Seok; Yang, Jung Yoon; Lee, Jooyun; Lee, Yu-Ri; Kim, Seong Soon; Kim, Geum Ran; Chae, Jin Sil; Ahn, Jin Hee; Shin, Dae-Seop; Choi, Tae-Young; Bae, Myung Ae
Highlights: In this study, we show that KDZ-001, a novel anti-melanogenic agent, strongly inhibits melanin synthesis in the developing melanophores of zebrafish, HMV-II cells, and reconstituted human skin with no toxicity. We also show that KDZ-001 directly inhibits TYR enzymatic activity. Thus, KDZ-001 is a potential candidate for a skin-whitening agent in the cosmetic industry. Abstract: Background: The demand for anti-melanogenic agents is increasing due to the unwanted side effects of current treatments. To find an effective anti-melanogenic agent, we used zebrafish as a whole animal model for phenotype-based drug and cosmetic discovery screening. Objectives: The aim of this study was to identify and explore a small molecule that could be used for skin-whitening cosmetics. Methods: Using zebrafish embryos, we examined the effects of 1000 compounds on zebrafish development and pigmentation. Pigmentation production was assessed by tyrosinase (TYR) enzymatic activity and melanin contents. Pigmentation marker expression in the human melanoma cell line HMV-II was analyzed by western blot. We also tested reconstituted human skin tissue and analyzed KDZ-001 with computational molecular modeling. Results: We identified three compounds that affected the pigmentation of developing melanophores in zebrafish. Among them, we identified KDZ-001, a novel anti-melanogenic agent, which strongly inhibits melanin synthesis in the developing melanophores of zebrafish, HMV-II cells, and reconstituted human skin with no toxicity. We found that KDZ-001 directly inhibits TYR enzymatic activity. Notably, computational molecular modeling of KDZ-001 suggested that its interaction with copper ions in the active site of TYR is essential for melanin synthesis, further demonstrating that KDZ-001 mainly acts as a TYR inhibitor to synthesize melanin. Conclusion: KDZ-001 inhibits melanin synthesis and has a potential for use in skin-whitening cosmetics.